A case of autoimmune hemolytic anemia following thrombocytopenia - Gürgey, Aytemiz; Özsoylu, Şinasi; Kanra, Tekin; Ertürk, Gülyüz (The Turkish Journal of Pediatrics, 1983)
A 9-year-old boy who first had thrombocytopenia and later developed leukopenia and Coombs’ positive hemolytic anemia is presented. In the light of this case, Evans’ syndrome is briefly reviewed. To our knowledge this case is unique from the standpoint that the antibodies related to Coombs’ positivity in our patient were more prominently related to the IgA class.